2020
DOI: 10.1002/cbf.3533
|View full text |Cite
|
Sign up to set email alerts
|

WWP2 ameliorates acute kidney injury by mediating p53 ubiquitylation and degradation

Abstract: E3 ubiquitin ligase gene, WWP2, is associated with acute kidney injury (AKI). This research was conducted to explore the role of WWP2 in AKI. AKI cell model was produced in human renal proximal tubular epithelial cell line (HK‐2) by ischemia‐reperfusion (IR) injury. CCK8 and flow cytometry assay were performed to explore the influence of WWP2 overexpression on cell proliferation and apoptosis of IR‐induced HK‐2 cells. Quantitative real‐time PCR and immunoblotting (IB) were performed to assess the gene and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Xu et al found that WWP2 siRNA inhibited Bcl-2 expression by promoting Bax and Caspase7/8 to induce apoptosis of liver cancer cells [ 53 ]. Even more, overexpression of WWP2 could inhibit the apoptosis of human renal tubular epithelial cells by inducing Bcl-2 expressionand and inhibiting Bax expression [ 40 ]. However, the regulatory mechanism of miR-328-5p and its target gene WWP2 in IDD has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu et al found that WWP2 siRNA inhibited Bcl-2 expression by promoting Bax and Caspase7/8 to induce apoptosis of liver cancer cells [ 53 ]. Even more, overexpression of WWP2 could inhibit the apoptosis of human renal tubular epithelial cells by inducing Bcl-2 expressionand and inhibiting Bax expression [ 40 ]. However, the regulatory mechanism of miR-328-5p and its target gene WWP2 in IDD has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was performed three times. Experiment is based on U6 and β -actin [ 40 ]. Gene expression was measured using the 2 −△△Ct .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein stability assay was according to the previous reports 20–22 . Briefly, the DMSO‐treated NEP cells (Day 7) and RE‐treated NEP cells (Day 7) were treated with an inhibitor of protein synthesis, cycloheximide (CHX, 100 μg/mL; Sigma, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The protein stability assay was according to the previous reports. 20 , 21 , 22 Briefly, the DMSO‐treated NEP cells (Day 7) and RE‐treated NEP cells (Day 7) were treated with an inhibitor of protein synthesis, cycloheximide (CHX, 100 μg/mL; Sigma, USA). The cells were obtained at indicated times for analysing the protein stability of NR2F1 by Western blotting.…”
Section: Methodsmentioning
confidence: 99%